Treatment and Displacement Affect the Reoperation Rate for Femoral Neck Fracture - Murphy, Donavan K. (Springer US, 2013)
BACKGROUND: Femoral neck fractures (FNFs) comprise 50% of geriatric hip fractures. Appropriate management requires surgeons to balance potential risks and associated healthcare costs with surgical treatment. Treatment complications can lead to reoperation resulting in increased patient risks and costs. Understanding etiologies of treatment failure and the population at risk may decrease reoperation rates. QUESTIONS/PURPOSES: We therefore (1) determined if treatment modality and/or displacement affected reoperation rates after FNF; and (2) identified factors associated with increased reoperation and timing and reasons for reoperation. METHODS: We reviewed 1411 records of patients older than 60 years treated for FNF with internal fixation or hemiarthroplasty between 1998 and 2009. We extracted patient age, sex, fracture classification, treatment modality and date, occurrence of and reasons for reoperation, comorbid conditions at the time of each surgery, and dates of death or last contact. Minimum followup was 12 months (median, 45 months; range, 12–157 months). RESULTS: Internal fixation (hazard ratio [HR], 6.38) and displacement (HR, 2.92) were independently associated with increased reoperation rates. The reoperation rate for nondisplaced fractures treated with fixation was 15% and for displaced fractures 38% after fixation and 7% after hemiarthroplasty. Most fractures treated with fixation underwent reoperation within 1 year primarily for nonunion. Most fractures treated with hemiarthroplasty underwent reoperation within 3 months, primarily for infection. CONCLUSIONS: Overall, hemiarthroplasty resulted in fewer reoperations versus internal fixation and displaced fractures underwent reoperation more than nondisplaced. Our data suggest there are fewer reoperations when treating elderly patients with displaced FNFs with hemiarthroplasty than with internal fixation. LEVEL OF EVIDENCE: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.